TEACHER'S STRATEGIES IN TEACHING ENGLISH AS A FOREIGN LANGUAGE TO PRIMARY SCHOOL STUDENTS - Sary, Fetty Poerwita (2006)
This observational study, which focuses on strategies used by teachers when teaching English as a Foreign Language to primary school students, was conducted in two classes at Al Azhar Syifa Budi Parahyangan International Islamic School. This study attempted to address the following question: what instructional strategies are used by the English teachers at Al Azhar Syifa Budi Parahyangan? The data, which were collected by using a classroom observation and interview with the teachers and their students, were analyzed qualitatively by using categories formulated based on theories related to instructional strategies include planning and preparing the instruction, implementing the teaching and learning process, and assessing the students' achievement. The major findings of this study include 1) although the teachers do the same stages in planning but the plan is implemented and resulted in different ways; 2) the teachers are able to use games as a tool for learning; 3) although curriculum requires teachers to integrate the skills (reading, listening, writing, and speaking), in actual implementation, the teachers do not teach English in integrative ways; 4) time management in this school has become a problematic factor for the teachers; 5) with respect to teacher's strategies in assessing students' achievement, the teachers do assessment by way of remedial teaching once a week after the class is over in part where the students failed to understand.